The Poland competitiveness and the trade connections in reference to the countries of Central and Eastern Europe and former USSR - Maceikianec, Tadeusz (Comparative Economic Research. Central and Eastern Europe, 2010)
In the paper is presented multiaspectual indicatory statistical analysis (TI, RCA, IIT, ESI) of the Polish trade with the countries of Central and Eastern Europe and former USSR in the reference to UE-15 countries. The chosen group of countries encloses all the former republics of the USSR (Armenia, Azerbaijan, Belarus, Estonia, Georgia, Kazakhstan, Kyrgyzstan, Lithuania, Latvia, Moldova, Russia, Tajikistan, Turkmenistan, Ukraine, Uzbekistan) and Bulgaria, Czech Republic, Romania, Hungary, Slovakia. Studied countries were divided into two groups - UE and non UE. It was showed that in the first group had appeared a tendency to levelling the competitiveness and to the growth of cooperation, in second however the level of cooperation is close to the zero and the level of competitiveness diminishes in relation to Poland. 1.